Uporaba odpadne plastike za izdelavo lepil za lepljenje lesa - Šernek, Milan (Les (Ljubljana), 2020)
There is more and more plastic waste, so we try to find different ways to recycle and reuse it. Recycled thermoplastic polymers represent an interesting potential for the production of adhesives, so the aim of our preliminary investigations was to examine the suitability of waste polystyrene for the production of adhesives for wood bonding. The adhesive mixtures were prepared by cutting the waste polystyrene cups (L) and coffee spoons (Ž) into smaller pieces and dissolving them separately in 5 different solvents: Butyl acetate (BA), Dimethylformamide (DMF), Tetrahydrofuran (THF), Limonene (L) and Acetone (AC). From these we prepared composite samples of two beech lamellae (Fagus sylvatica L.), which were pressed for 10 minutes in a hydraulic press at a temperature of 150 °C and a pressure of 12 bar. In order to determine the quality of the bonding, we carried out a shear test with a Zwick/Roell Z005 universal testing machine. We found that the test specimens bonded with the adhesive mixture Ž-DMF achieved an average shear strength of 6.5 N/mm2 and the test specimens bonded with L-DMF achieved 3.8 N/mm2. All other test specimens showed a lower strength of the adhesive bonds, or they mostly delaminated after hot pressing or later during sawing into test specimens. In further research work we will modify these promising adhesive mixtures and optimize the pressing parameters in order to achieve bonding quality that meets the standard requirements for thermoplastic adhesives for interior applications.
Keywords: adhesive; lepilo; les; odpadna plastika; polistiren; polystyrene; ponovna uporaba plastike; reuse of plastic; shear strength; strižna trdnost; waste plastics; wood